Sistem Deteksi Dini Banjir Berbasis Geographic Information System Terintegrasi Cloud Computing Website Di Kelurahan Tambakkemerakan - Mochammad Rifki Ulil Albaab; Rangga Raditya Nugroho; Junia Vitasari; Johan Krisbima Abi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Based on the 2021 BNPB report, the flood disaster in Sidoarjo Regency, including Tambakkemerakan Village, had a significant impact with 1,205 families affected, 52 houses submerged and 2,449 hectares of land inundated. Infrastructure such as bridges, roads and drainage systems also suffered damage. The difficulty of getting real-time information regarding the location and water level at flood points makes it difficult for people to prepare themselves and take appropriate action. Therefore, the aim of this research is to increase community preparedness and reduce losses due to flooding by providing real-time early warning information. The research method involves system innovation that is integrated with the Geographic Information System and website, as well as organizing outreach and training to the community. The research results show that this solution is successful in providing better accessibility to information regarding the height of flood water and its status at the location points where the tool has been installed in real-time, enabling quick decision making, and reducing the impact of material and non-material losses.